The harmful Effects of Monosodium Glutamate on Blood Parameters Liver and Kidney Functions In Adult White Rats and the Protective Role of Omega-3 - Thoalffakar A. ALhamed; Farah A. Al-marzook; Abdulridha Mohammed Al-Asady (Indian Journal of Forensic Medicine & Toxicology, 2021)
The present study was conducted to find out the harmful effect of exposure to monosodium glutamate(MSG) on laboratory animal weight, hematological and biochemical parameters on rats of 10 -15 weeksold and weight of 100-200 g. Whereas, this study was conducted in the Basic Sciences Branch - College ofNursing - University of Warith Alanbiyaa From 11/1/2019 to 2/1/2020, the animals were divided into fourgroupsG 1- Control The first group controlG 2- MSG (1.8mg / kg) Group IIG 3 - MSG (1.8 mg / kg) + omega-3 (0.8 mg / kg) Group IIIG 4 - MSG (1.8 mg / kg) + omega-3 (1.2 mg / kg) Group IVWhere the four groups were fed according toThe above distribution is according to the concentrations in each group effect of MSG at one oral low doseof 1.8 mg/g body wt. on liver and kidney functions in albino rats. The possible protective effect of omega3 (at oral dose of 0.8 mg/g body wt.) (at oral dose of 1.2 mg/g body wt.) against MSG induced hepatic andrenal stress was also investigated of mono-sodium glutamate for 30 days.The results showed a significant decrease (p <0.05) in blood parameters, including RBC count 5.1 ±0.7 andconcentration of PCV: 14.5 ±0.33, MCH: 34.5 ± 2.77, MCV: 96.5 ±3.21, MCHC: 34.0 ± 0.89. Comparedwith the control group indicating anemia in MSG treated animals.There was a significant increase in the biochemical parameters (AST: 216 ± 14.8, ALT 3.6 ± 0.40, ALP144.75± 6.55). And also in the Urea - Creatinine kidney standardsWhich represents the liver function in animals treated with monosodium glutamate compared with thecontrol group, despite a significant increase (P <0.05) in the level of urea 2.70 ± 0.07 and creatinine 0.098 ±0.005 in the blood in the animal treated with MSG compared with the control group.